(untitled) (The Pakistan Development Review, 1987)
Important restrictions, both tariff and non-tariff, have been the main policy instrument in implementing the import substitution industrial strategy which has been pursued by almost all the developing countries. The strategy was visualised as a means of realising higher growth of output and foreign exchange earnings, conservation of foreign exchange and stability of the economy. Efficiency in resource use and income distribution considerations did not assume much significance in the development strategy. The industrial sector of Pakistan, protected from imports through severe quantitative restrictions and even bans, suffered from inefficiencies and rigidities. However, this was realized only by the mid-Sixties when Soligo and Stern (1985), on the basis of effective protection rates reached a very startling, though not entirely correct, conclusion that in most of the industries in Pakistan, value added at world market prices was negative! . The study aroused interest in the examination of efficiency levels, both inside and outside Pakistan, through the computation of effective protection rates. These studies include among others, Balassa (1971); Little, Scitovsky and Scott (1970) and the NBER series on the import regime in many countries. Studies relating to effective protection in Pakistan include Soligo and Stern (1985); Lewis and GUisinger (1968); Kemal (1978); Khan (1978) and Naqvi, Kemal and Heston (1983).